Strategic change and adaptation in the context of dynamic capacity development (Research, Society and Development, 2020)
This study aims to understand the process of change and strategic adaptation of a family business focused on the management of health units, located in the northwest of Rio Grande do Sul, in the period between 2013 and 2018. It seeks to understand the critical periods existing in the organization's history and what dynamic capabilities prevail at those times. As for the methodological aspects, this is a unique case study, of descriptive nature and qualitative approach. The periods of strategic change were analyzed from the dimensions proposed by Pettigrew, Ferlie and Mckee (1992), context, content and process and through longitudinal and historical analysis through direct research procedures (Mintzberg, 1983). With the realization of the study, it was possible to characterize the organization's history in four strategic periods: Birth (2013-2014), Critical period (2015), Reflections and repositioning (2016) and Reorganization of organizational structure (2017-2018). The analyzes pointed out that the dynamic capacities that had an emphasis in each period were respectively: absorptive capacity, adaptive capacity, absorptive capacity and adaptive capacity. The organization has demonstrated, therefore, internal competences and receptivity to the demands of new services from the environment by the users of the services themselves. In each period it was able to reorganize its resources and competences and shows indications of search also of the development of the innovative capacity.